2021
DOI: 10.3390/ijerph182413400
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Functional Training (HIFT) Improves Fitness in Recruit Firefighters

Abstract: Background: Firefighting is a strenuous profession requiring adequate levels of fitness for effective job performance. Providing firefighters with a safe and effective fitness program is essential for optimal performance. The purpose of this project was to examine changes in various parameters of physical fitness and firefighter ability following a 7-week high intensity functional training (HIFT) program. Methods: Participants were male firefighter recruits (N = 89; age = 27.1 ± 4.2 years, height = 1.78 ± 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 37 publications
(91 reference statements)
3
37
0
Order By: Relevance
“…The purpose of this study was to determine the effect of an acute bout of HIRT on subsequent occupational performance and to determine the time course of recovery. This research is critical given the NFPA's recommendation to perform on-duty exercise (30), the high prevalence of firefighters using HIRT (19), and the efficacy of HIRT to enhance occupational readiness (6). Regarding group-level analysis, participation in a HIRT session reduced multiple performance metrics on a maximally paced SFGT 10min but not SFGT 60min .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to determine the effect of an acute bout of HIRT on subsequent occupational performance and to determine the time course of recovery. This research is critical given the NFPA's recommendation to perform on-duty exercise (30), the high prevalence of firefighters using HIRT (19), and the efficacy of HIRT to enhance occupational readiness (6). Regarding group-level analysis, participation in a HIRT session reduced multiple performance metrics on a maximally paced SFGT 10min but not SFGT 60min .…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence supporting the efficacy of HIRT for structural firefighters. For instance, Chizewski et al (6) used HIRT in a portion of a 7-week training intervention in firefighter recruits and demonstrated increased firefighter physical ability, decreased body mass index (BMI), and improved cardiovascular and muscular endurance. High-intensity resistance training has also been demonstrated to be effective for military personnel because HIRT has been shown to increase metabolic and physiological adaptations that are associated with muscular strength, body composition, and general physical preparedness for uncertain situations (17).…”
Section: Introductionmentioning
confidence: 99%
“…Although their organizations conduct these periodic physical fitness evaluations to evaluate their fitness and estimate their readiness for job tasks, the proportion of physiologically fit individuals remains low. Low aerobic capacity could be improved through physical training programs and an increase in physical activity [ 11 , 35 , 36 , 37 ]. A meta-analysis study showed that an exercise intervention, including aerobic exercise, resistance exercise, or a combined method of 3–4 sessions/weeks for 16.5 ± 10 weeks, could improve aerobic capacity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study showed that an exercise intervention, including aerobic exercise, resistance exercise, or a combined method of 3–4 sessions/weeks for 16.5 ± 10 weeks, could improve aerobic capacity [ 35 ]. Chizewski et al [ 11 , 37 ] reported that high-intensity fitness training improved fitness and firefighting ability [ 37 ]. After performing a fitness training program for seven weeks, VO2 max increased from 40.84 ± 5.09 in the first week to 45.30 ± 5.24 in the seventh week [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three researchers conducted the fitness assessments throughout the study, and the same tester performed assessments on the same group of subjects to maintain congruity between tester and subject 23,34 . For reference, these researchers possessed advanced degrees in exercise physiology, certifications from the American Council on Exercise, American College of Sports Medicine, and National Strength and Conditioning Association, and had extensive experience with physical fitness testing (approximately 30 combined years).…”
Section: Methodsmentioning
confidence: 99%